2019
DOI: 10.1073/pnas.1816076116
|View full text |Cite
|
Sign up to set email alerts
|

The mixed effects of online diversity training

Abstract: We present results from a large (n = 3,016) field experiment at a global organization testing whether a brief science-based online diversity training can change attitudes and behaviors toward women in the workplace. Our preregistered field experiment included an active placebo control and measured participants’ attitudes and real workplace decisions up to 20 weeks postintervention. Among groups whose average untreated attitudes—whereas still supportive of women—were relatively less supportive of women than oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(177 citation statements)
references
References 32 publications
6
169
1
1
Order By: Relevance
“…Past research has found that people often react negatively to explicit attempts to increase diversity (Plant and Devine 2001, Legault et al 2011, Dobbin et al 2015 and that it is challenging to change people's biases and stereotypes (Kalev et al 2006, Lai et al 2016, Chang et al 2019, Forscher et al 2019. Prompting people to make collective rather than isolated decisions is a novel approach to increasing diversity in that it does not involve reprimands or explicit directives (which can be viewed as overly paternalistic), Chang et al: The Isolated Choice Effect Management Science, 2020, vol.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has found that people often react negatively to explicit attempts to increase diversity (Plant and Devine 2001, Legault et al 2011, Dobbin et al 2015 and that it is challenging to change people's biases and stereotypes (Kalev et al 2006, Lai et al 2016, Chang et al 2019, Forscher et al 2019. Prompting people to make collective rather than isolated decisions is a novel approach to increasing diversity in that it does not involve reprimands or explicit directives (which can be viewed as overly paternalistic), Chang et al: The Isolated Choice Effect Management Science, 2020, vol.…”
Section: Discussionmentioning
confidence: 99%
“…Similar null or negative effects were found for retention and promotion of women and minorities in U.S. federal agencies (Kellogh & Naff, ). More recently, an international field experiment assessed the effects of diversity training on both attitudes and behavior by enrolling volunteers at a multinational company in a bias training program and assessing behavior surreptitiously at a later date (Chang et al., ). Diversity training focused on gender or racial bias (vs. a control training) led to modest decreases in bias among non‐Americans and those with low initial levels of bias, but the intervention did not affect bias among Americans or among those with high levels of initial bias.…”
Section: Approaches To Organizational Diversity Managementmentioning
confidence: 99%
“…These strategies may work well with individuals who are motivated to reduce prejudice and prevent discrimination, but may not be effective at creating more fair workplaces among those with higher levels of prejudice or who believe that discrimination is not a problem in their workplace (Chang et al., ). Some critics of diversity training note that attempts to reduce prejudice will only be successful for those with already low levels of prejudice, and that the efforts will likely be ineffective or counterproductive among those high in prejudice (Noon, ).…”
Section: Social Issues and Policy Implicationsmentioning
confidence: 99%
“…Consistent with this assessment, research on the efficacy of anti-bias training paints a decidedly mixed picture. Various studies have concluded that the most popular programs and policies have little impact on diversity outcomes (Bradley et al, 2018;Chang et al, 2019;Kalev et al, 2006). More than that, in some cases, anti-bias interventions may backfire, increasing rather than reducing bias (Duguid & Thomas-Hunt, 2015;Moss-Racusin et al, 2014;Vorauer, 2012).…”
Section: Anti-bias Trainingmentioning
confidence: 99%